KINEMATICS AND DYNAMICS MANIPULATOR - Квасніков, В. П.; Вохмянін, М. М. (Science-based technologies, 2009)
Robots which must work in the real world require some way to manipulate objects; pick up, modify, destroy or otherwise have an effect. Thus the ‘hands’ of a robot are often referred to as end-effectors, while the arm is referred to as a manipulator. A common effector is the gripper. In its simplest manifestation it consists of just two fingers which can open and close to pick up and let go of a range of small objects. Some advanced robots are beginning to use fully humanoid hands. These highly dexterous manipulators, with as many as 20 degrees of freedom and hundreds of tactile sensors can be difficult to control. The computer must consider a great deal of information, and decide on the best way to manipulate an object from many possibilities.